Microbial biofilms - part I: Ecological and genetical aspects - Ivanović Mirjana; Vučetić Mirjana (Serbian Medical Society - Dental Section, Belgrade, 2006)
Relatively new advances in microscopy and molecular technology have made possible studying of bacterial communities in situ. Natural bacterial associations in biofilm matrix function as cooperative consortia in a complex but synchronized manner. Regardless of formation, biofilms are developing in a multicellular pattern. Microcolonies forming a biofilm can be populations of a single species or multi-species bacterial communities influenced by environmental parameters. Numerous conditions, such as characteristics of the surface and interactions, availability of nutrients, composition of microbial community and hydrodynamics may influence the structure of a biofilm. Implementation of molecular methods in understanding of oral flora and its features is making shifts in our dental plaque knowledge. .